A influência da reflexividade verbal no processamento anafórico - Henrique, Judithe Genuíno (2016)
The research conducted in this study investigates the verbal reflexivity and its role in the anaphoric process. In order to determine which verbs are considered more acceptable in reading sentences containing the anaphora a si mesmo(a) and se(self), it was held three offline acceptability judgment tests with Brazilian Portuguese native speakers. It was used the concept of reflexivity proposed by Reinhart & Reuland (1993) which predicts that the reflectivity is a property of predicates as well as the functionalist nature of the work of Christiano (1993) and Mello (2008), as they established a higher rating categorical for verbs with more reflective characteristics, dividing them into three levels; primary – penteou (combed), secondary – sentou (sat) - and tertiary – acusou (accused) - according to their degree of reflexivity. The results found in the first test with anaphora a si mesmo(a), and se, and the three verbs with the three levels of reflexivity showed that the anaphora se was considered more acceptable, regardless of the verb type. With these results, we conducted two tests in order to verify the possible verbal influence. In the second test using the same verbs of the first experimental test and the anaphora se, in order to find evidences of the verbal influence. The findings toward to the influence only of the secondary verb combined with anaphora se. Thus, we conducted a third trial acceptability test using only the secondary verb and the absence and presence of anaphora se and we observe a significant effect of the secondary verb type when it was in the presence of anaphora is. In general, the results showed that the property of reflexivity may be present both in the anaphora as the predicate, and says Reinhart & Reuland (1993).